Social Work Skills in Working with Survivors of Earthquake: A Social Work Intervention - Iran - Mohammad Reza Iravani (Social Work & Society, 2005)
The Loss, grief and other problems are events that most of people experience them during their Life. The earthquake is a disaster that makes people experience loss, grief and problems simultaneously. This crisis affects on survivors as much as they face to dangers in their lives. Thus, most of them need to being supported until they can solve their problems, be relaxed and do their daily activities. We know that the profession of social workers is to assist individuals who are seeking help. But there is a Problem, how do they help the clients efficiently? Especially, those clients who have suffered earthquake. Generally, the role of social workers in helping the survivors of earthquake is significant. To this end, the present paper tries to describe the process of social casework and those skills required for social workers to help the survivors. These skills include: situational supporting, hopefulness making, consoling, assuring, concentrating, solutions developing and refer.